Automatic review identification on the web using pattern recognition. (14th August 2012) - van der Meer, Jeroen; Frasincar, Flavius
SUMMARY: In this paper we propose the Automatic Review Recognition and annOtation of Webpages method, which is capable of identifying and annotating user submitted reviews on a Web page. The method consists of six steps: data preparation, page‐level pattern identification, subjectivity analysis, container structure analysis, review properties identification, and review annotation. For the evaluation, we have implemented the method and tested it on various review websites. On the basis of the performed evaluation, we conclude that our method is capable of identifying and annotating the majority of reviews. Copyright © 2012 John Wiley & Sons, Ltd.